2016
DOI: 10.1002/pon.4206
|View full text |Cite
|
Sign up to set email alerts
|

Cancer diagnosis disclosure preferences of family caregivers of cancer patients in Egypt

Abstract: The results suggest that the majority of FCs of Egyptian cancer patients prefer CDD to patients. The finding that the vast majority of FCs of aware patients preferred CDD suggests that the reaction of Egyptian patients to CDD is acceptable by FCs. Family caregivers with a negative attitude toward CDD may be reflecting their own fears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 21 publications
9
24
0
Order By: Relevance
“…The social structure of the region is based usually on the importance of the family bonds instead of the individual autonomy 7 . In our study, the majority of patients (84%) were aware of their cancer diagnosis, consistent with the results of another study from Egypt that included family caregivers 8 . The prevalence of awareness of diagnosis among cancer patients varies widely from a country to another.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The social structure of the region is based usually on the importance of the family bonds instead of the individual autonomy 7 . In our study, the majority of patients (84%) were aware of their cancer diagnosis, consistent with the results of another study from Egypt that included family caregivers 8 . The prevalence of awareness of diagnosis among cancer patients varies widely from a country to another.…”
Section: Resultssupporting
confidence: 80%
“…Another factor that may have contributed to the unawareness of some of our patients is their families' negative attitude towards truth-telling. In context, a recent Egyptian research revealed that some of family caregivers preferred not to disclose cancer diagnosis to patients, but , the majority preferred truth-telling 8 . Besides our cultural and religious codes, legislations should assure our patient's right to have an informed consent which should be applied in the Middle Eastern countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses suggested that medical teams should communicate with patients' family members and try to influence their attitudes toward truth telling. A similar suggestion was made in Alsirafy's study . Medical staff were recommended to enquire about the reasons underlying why family members conceal diagnoses from patients.…”
Section: Resultsmentioning
confidence: 74%
“…In many areas of the world, family members have been reported to be an obstacle to CDD to patients by asking medical professionals not to tell the truth . In our former study, family members preferred to hide cancer diagnoses from patients to protect them from perceived emotional harm …”
Section: Resultsmentioning
confidence: 79%